Evaluation of Acute and Subacute Toxicity of Alcoholic Extract of Whole Plant of Phyllanthus rheedii - Sivajothi, V.; Dey, Akalanka; Jaykar, B. (Asian Journal of Chemistry, 2010)
Present studies reports the acute and subacute toxicity of alcoholic (95 %) extract of whole plant of Phyllanthus rheedii in Swiss mice and Wister albino rats. The mice were divided into 5 groups of 10 animals and each group received once 100, 500, 1000, 2000 and 3000 mg/kg dose of extract by intra-gastric gavages for 1 d. For the sub acute toxicity, four groups of 6 rats (3 males and 3 females) were received distilled water (control), 125, 250 or 500 mg/kg of extract every 24 h orally for 28 d. The results indicated that the LD50 of the extract was about 2588 mg/kg of body weight. No significant variation (p < 0.05) in the body and organ weights between the control and the treated group was observed after 28 days of treatment. Hematological analysis and clinical blood chemistry revealed no toxicity effects of the extract. Pathologically, neither gross abnormalities nor histopathological changes were observed. No mortality was recorded in 28 days. Phyllanthus rheedii extract was found to be fairly nontoxic.